Stage I HPV‐positive oropharyngeal cancer: Should all patients receive similar treatments?. Issue 1 (19th September 2019) - Yoshida, Emi J.; Luu, Michael; Mallen‐St. Clair, Jon; Mita, Alain C.; Scher, Kevin S.; Lu, Diana J.; Nguyen, Anthony T.; Shiao, Stephen L.; Ho, Allen S.; Zumsteg, Zachary S.
Abstract : Background: Patients with clinical stage I human papillomavirus (HPV)–positive oropharyngeal squamous cell cancer (OPSCC) according to the American Joint Committee on Cancer (AJCC) eighth edition classification comprise a heterogeneous group formerly classified as stage I to stage IVA according to the seventh edition of the AJCC classification. These patients historically were treated with disparate treatment regimens, particularly with respect to the use of concurrent chemotherapy. Methods: The National Cancer Data Base was queried for patients with AJCC eighth edition clinical stage I HPV‐positive OPSCC (AJCC seventh edition stage T1‐2N0‐2bM0) who were diagnosed from 2010 to 2014 and underwent definitive radiotherapy. Concurrent chemotherapy with definitive radiotherapy was defined as chemotherapy administered within 7 days of the initiation of radiotherapy. Results: The current analysis included 4473 patients with HPV‐positive stage I OPSCC with a median follow‐up of 36.3 months. A total of 3127 patients (69.9%) received concurrent chemotherapy. Concurrent chemotherapy was found to be associated with improved overall survival on multivariable analyses (hazard ratio [HR], 0.782; 95% CI, 0.645‐0.948 [ P  = .012]). The effect of chemotherapy on survival varied based on lymph node involvement ( P for interaction = .001). Specifically, chemotherapy was associated with improved survival for patients with lymph node–positive stage I disease (stage III‐IVA according to the AJCC seventh edition: HR, 0.682; 95% CI, 0.557‐0.835 [ P  < .001]), but not for patients with N0 disease (stage I‐II according to the AJCC seventh edition: HR, 1.646; 95% CI, 1.011‐2.681 [ P  = .05]). Similar results were noted among propensity score–matched cohorts. Conclusions: Treatment with concurrent chemotherapy was associated with improved overall survival for patients with lymph node–positive, but not lymph node–negative, AJCC eighth edition stage I HPV‐positive OPSCC undergoing definitive radiotherapy, thereby supporting different treatment paradigms for these patients. Abstract : Treatment with concurrent chemotherapy appears to be associated with improved overall survival among patients with American Joint Committee on Cancer (AJCC) eighth edition stage I human papillomavirus–positive oropharyngeal squamous cell carcinoma undergoing definitive radiation. In the current study, this association is noted exclusively among patients with lymph node involvement, which previously was classified as stage III to stage IVA disease in the AJCC seventh edition staging system, thereby supporting different treatment paradigms for these patients.